The Overview of Menstrual Physiology: A Narr ative Literature Review - Andini, Kusuma (Sriwijaya Journal of Obstetrics and Gynecology, 2023)
Menstruation is a physiological or normal condition, namely events of the production of bl ood, mucus, and cell waste periodically originate from the uterine mucosa and occur relatively regularly from menarche until menopause, exc ept during pregnancy and lactation. Menstruation is the result of very n eat and standard cooperation from the hypothalamus-pituitary-ovarian endocrine axis. Hypothalamus spurs the pituitary gland by secreting gonad otropin-releasing hormone (GnRH), a deca-peptide secreted pulsatively by the hypothalamus. Menstruation is considered normal if it occurs between 22-35 days. Disturbance menstruation is most common at the beginning and end of the reproductive period, namely in those under 19 years of age and over 39 years of age. These disturbances may be related to the length of t he menstrual cycle or the number and duration of menstruation. One person Women can experience both disorders. This literature review aimed to describe the menstrual cycle physiologically and the disorders that accompany it.